Teaching performance at private universities in Medan City: Analysis of factors affecting university governance - Januri; Maksum, Azhar; Muda, Iskandar; Bukit, Rina Br (International Journal of Innovative Research and Scientific Studies, 2023)
The purpose of this research is to find out what factors influence the performance of tertiary institutions in obtaining accreditation. A structural Equation Model (SEM) is used for data analysis. The data processing tool in the buying and selling model in this study uses Partial Least Squares (PLS). The research design is causal research and the variables used are the performance of private universities governance, funding, internal audit, participation in budgeting and risk management. The results of the study show that internal audit has an impact on university governance. Budget participation and risk management have a positive effect on good university governance while financing and internal audit have a negative effect on university performance. Empirical evidence analyzes the effect of risk management on university performance at private universities in Medan City.